Perbedaan Keberhasilan Inseminasi Buatan Menggunakan Semen Beku Dan Semen Cair Menggunakanpengencer Cep-3 + Kuning Telurpada Sapi Persilangan Ongole - Ahmad Salim; Aulia Puspita Anugra Yekti; Kuswati Kuswati; Trinil Susilawati (TERNAK TROPIKA Journal of Tropical Animal Production, 2018)
Abstract: The purpose of this research was to investigate the successful difference of artificial insemination (AI) using frozen semen and liquid semen with CEP-3 + egg yolk diluent of Ongole Crossbred cow indicated by Non Return Rate (NRR) and Conception Rate (CR). The materials used were 54 heads of cow which selected purposively using some criteria such as healthy, free from any reproduction disorder and having at least sexual desire criteria 3A (red, swollen and warm). This field experiment consisted of direct observation and interview to acquire primary and secondary data. The datas were analyzed descriptively and continued by   Chi-square test. The results showed that the value of NRR was insignificant influenced between the two treatment. The Conception Rate for frozen semen and liquid semen was found 62.96% and 51.85% respectively. The conclusion of this experiment was the successful rate of artificial insemination (AI) using liquid semen with the CEP-3 + 20% egg yolk diluent was lower than artificial insemination using frozen semen. The value of Conception Rate of frozen semen treatment was 62.96% and the liquid semen treatment was 51.85%.